2021
DOI: 10.2217/pmt-2021-0045
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency (10 kHz) Spinal Cord Stimulation for the Treatment of Focal, Chronic Postsurgical Neuropathic Pain: Results from a Prospective Study in Belgium

Abstract: Aim: Chronic postsurgical pain (CPSP) is a common complication of surgery. This study was conducted to evaluate the efficacy and safety of paresthesia-free, 10-kHz spinal cord stimulation (SCS) as a treatment for CPSP. Patients & methods: Subjects in this prospective, single-arm study had an average pain intensity of ≥5 cm on a 10-cm visual analog scale. The subjects who had pain relief of ≥50% (response) with temporary trial stimulation were permanently implanted with 10-kHz SCS and assessed for 1 year. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“… 6 , 11 Among these SCS techniques, 10-kHz SCS was reported to decrease the mean pain score by >70% in more than 70% of patients with CPSP. 2 , 9 , 12 In our case, DTM SCS achieved 80% to 90% pain reduction of the CPSP on NRS at 3 months, which implies that DTM SCS is comparable to10-kHz SCS for the treatment of CPSP. Therefore, DTM SCS, similar to 10-kHz SCS, is expected to be a more optimal treatment option than tonic SCS, considering its efficacy, which is approximately a 50% pain reduction in the pain score of 50% of patients with other pain conditions.…”
Section: Discussionsupporting
confidence: 56%
“… 6 , 11 Among these SCS techniques, 10-kHz SCS was reported to decrease the mean pain score by >70% in more than 70% of patients with CPSP. 2 , 9 , 12 In our case, DTM SCS achieved 80% to 90% pain reduction of the CPSP on NRS at 3 months, which implies that DTM SCS is comparable to10-kHz SCS for the treatment of CPSP. Therefore, DTM SCS, similar to 10-kHz SCS, is expected to be a more optimal treatment option than tonic SCS, considering its efficacy, which is approximately a 50% pain reduction in the pain score of 50% of patients with other pain conditions.…”
Section: Discussionsupporting
confidence: 56%
“…According to Xu and colleagues, for patients with refractory PDN in the lower extremities, “SCS should be considered to reduce pain and improve quality of life.” 84 D’Souza and colleagues stated that SCS should be offered to patients who have refractory PDN and fail to benefit from conservative options, such as optimization of glucose control and neuropathic analgesic medications, before strong opioids are prescribed. 2 Meanwhile, current evidence favors a shift away from traditional SCS and toward paresthesia-free HF SCS 99 as first-line neuromodulation treatment 72,100 based on an accumulation of evidence showing better outcomes for HF SCS compared with traditional SCS 101-103 for many types of pain, including PDN.…”
Section: Current Recommendations For Using Scs For Pdnmentioning
confidence: 99%
“…Yet, recent advancements in technology and innovation in waveforms have yielded robust high-level clinical results, leading to the proposal for utilization of SCS earlier in the chronic pain treatment algorithm and for a broader range of painful conditions, such as painful diabetic neuropathy (PDN), chronic refractory neck pain, nonsurgical refractory back pain, in addition to FBSS and CRPS [13,14]. In particular, studies evaluating high-frequency (10 kHz) SCS for CLBP have demonstrated statistically significant and clinically meaningful improvement in pain and disability alone or when compared to conservative care [15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%